Photoactivated cell-killing involving a low molecular weight, donor–acceptor diphenylacetylene. Issue 17 (29th March 2019) - Chisholm, David R.; Lamb, Rebecca; Pallett, Tommy; Affleck, Valerie; Holden, Claire; Marrison, Joanne; O'Toole, Peter; Ashton, Peter D.; Newling, Katherine; Steffen, Andreas; Nelson, Amanda K.; Mahler, Christoph; et al.
Abstract : Drug-like, donor–acceptor diphenylacetylenes cause efficient cell death upon photoactivation and hence have potential phototherapeutic applications. Abstract : Photoactivation of photosensitisers can be utilised to elicit the production of ROS, for potential therapeutic applications, including the destruction of diseased tissues and tumours. A novel class of photosensitiser, exemplified byDC324, has been designed possessing a modular, low molecular weight and 'drug-like' structure which is bioavailable and can be photoactivated by UV-A/405 nm or corresponding two-photon absorption of near-IR (800 nm) light, resulting in powerful cytotoxic activity, ostensibly through the production of ROS in a cellular environment. A variety of in vitro cellular assays confirmed ROS formation and in vivo cytotoxic activity was exemplified via irradiation and subsequent targeted destruction of specific areas of a zebrafish embryo.